Development of Learning Instrument to Increase Student’s Physics Concept Mastery Through Conflict Cognitive Approach - Muh Makhrus; Wahyudi Wahyudi; Ahmad Busyairi; Haerunnisa Haerunnisa; Muhammad Zuhdi (Postgraduate, University of Mataram, 2022)
Physics learning using direct instruction method or speech method did not optimal in increasing concept mastery. This case results in low learning outcomes due to the low mastery of students' physics concepts. The solution to this problem is to develop learning instruments based on a cognitive conflict approach assisted by lesson videos to improve students' mastery of physics concepts as valid and appropriate products for use in learning. The learning tools developed are syllabus, lesson plans, Student’s Worksheet, lesson videos and concept mastery assessment instruments. The kind of research is research and development with the 4D method (define, design, develop, disseminate). This research is limited to the development stage, which includes validity testing. The results of this study can be concluded that the learning tools in the category are very valid and reliable. Based on these results, the learning tools developed are suitable for use in learning.